ASK2 Bioactive Compound Inhibits MDR Klebsiella pneumoniae by Antibiofilm Activity, Modulating Macrophage Cytokines and Opsonophagocytosis - Lalitha, Cheepurupalli; Raman, Thiagarajan; Rathore, Sudarshan S.; Ramar, Manikandan; Munusamy, Arumugam; Ramakrishnan, Jayapradha (Frontiers in Cellular and Infection Microbiology, 2017)
The emergence and spread of pathogens harbouring extended spectrum beta-lactamase (ESBL) like carbapenem resistant Gram negative bacteria are the major emerging threat to public health. Of particular concern Klebsiella pneumoniae carbapenamase- producing strains have been recorded worldwide. Catheter related urinary tract infections caused by K. pneumoniae are significantly associated with morbidity and mortality. Hence the present work was aimed to develop a strategy for addressing these issues through an innovative approach of antibiofilm and immunomodulation. These two independent activities were analysed in a Streptomyces derived ASK2 bioactive compound. While analysing the effect of sub-minimum inhibitory concentrations (sub-MICs), 0.5x of Minimum Inhibitory Concentration (MIC) was found to be more effective in preventing biofilm formation on coverslip and silicone catheter. The minimum biofilm eradication concentration (MBEC) was found to be 15-fold higher MIC with eradication of 75% of 3 day old biofilm. Apart from its antibiofilm potential, ASK2 also acts as an opsonin and enhances phagocytic response of macrophages against multidrug resistant K. pneumoniae. In addition, ASK2 resulted in elevated levels of nitric oxide generation by the macrophages and has a stimulating effect on IL-12, IFN-γ and TNF-α proinflammatory cytokines. The opsonic role of ASK2 and its potential in modulating proinflammatory cytokines secreted by macrophages implies the importance of ASK2 in modulating cellular immune response of macrophages against MDR K. pneumoniae. The present study proposes ASK2 as a promising candidate for treating MDR K. pneumoniae infections with its dual properties of antibiofilm and immunomodulatory activities.